Experimental Study of the Condenser of an Automotive Air Conditioner with Non-uniform Inlet Air Velocity - Liu Yusheng; Li Wanyong; Shi Junye; Chen Jiangping; Teng Shizheng; He Liu (Zhileng xuebao)
The condenser is one of the important components in an automotive air conditioning system. A traditional condenser is designed on the premise that the inlet air volume is evenly distributed. However, in reality, condenser inlet air is not uniform due to the presence of the anti-collision beam, which makes the thermal performance rapidly decline. In this paper, a new design of condenser layout was studied. The middle region is the superheating area, the upper and middle lower parts are the two-phase area, and the lower part is the super cooling area, which expresses the maximum heat dissipation potential of the condenser. Experimental analyses demonstrated that the heat exchange capacity, COP, system flowrate, and other comprehensive performance indices of the condenser with new process layout were 10%–15% higher than a traditional condenser. Furthermore, this enhancement in performance was greater in the presence of a car anti-collision beam. The cooling effect of the condenser was 4 °C higher than that of the original construction, which greatly reduced the influence of the uneven distribution of air velocity caused by the car’s anti-collision beam on system performance.